Mistake the vitiating element of a contract / Abdul Razak Abdul Aziz - Abdul Aziz, Abdul Razak (Faculty of Law, 1983)
Mistake is possibly the most obscure part of the law of contract. The 'textbook writers for instance Cheshire Fifoot and Anson suggest that mistake is a. magic doctrine in English law which may avoid a contract even where an offer has been accepted in its identical terms. Judges frequently use the word mistake but it is submitted that mistake itself is irrelevent at law. It may only be a ground for affording a party, some relief in Equity. A contract can only be void in law if there are elements which would prevent the parties to it from being ad idem. It could pe therefore be said that the meaning of mistake at law is very restrictive. This restrictive scope is adopted by the English Legal System. At law mistake as understood by a layman is not relevant. A layman might well believe that where a person enters into a contract under a misapprehension of certain, facts the contract should not be enforced. But, falling to the restrictive meaning, this cannot be so. The law does not declare a contract void merely because one or bctth parties would not have made it )lad the true facts been known.